Advanced Redox-Flow Batteries: A Perspective. Issue 1 (1st January 2016) - Perry, Mike L.; Weber, Adam Z.
Abstract : Redox-flow batteries are entering a period of renaissance, buoyed by both the increasing need for affordable large-scale energy-storage solutions, as well as leveraging the advancements in flow-cell technology, mainly in polymer-electrolyte fuel cells. This perspective highlights the research-and-development avenues and opportunities for redox-flow-battery cells and materials.